Antiseptic Liquid Soap from Corn Oil (Zea mays L) and Aloe Vera Extract with The Variation of SLS (Sodium Lauryl Sulfate) (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2023)
Liquid soap is a cleaning agent made from a chemical reaction between potassium hydroxide and fatty acids from vegetable oils and animal fats. This study aims to determine the quality and formulation used in making antiseptic liquid soap from aloe vera with the variation of Sodium Lauryl Sulfate (SLS). Previous research on making liquid soap from aloe vera produced soap with free alkaline levels and a high pH and still lacking foam. In this study, liquid soap was made by adding variation of SLS (Sodium Lauryl Sulfate), as a foam booster and citric acid as a substance that can control the pH of the soap. The resulting liquid soap product was analyzed for pH value, foam stability, free alkali content/FFA, viscosity, density, ALT and bacterial test. The results showed that each soap formula produced match with the requirements of SNI 2588-2017 and the best formulation is the F2.